ATIM-08. TRIAL IN PROGRESS: CA209-9Y8 PHASE 2 TRIAL OF TUMOR TREATING FIELDS (TTFS), NIVOLUMAB PLUS/MINUS IPILIMUMAB FOR BEVACIZUMAB-NAÏVE, RECURRENT GLIOBLASTOMA. (11th November 2019) - Odia, Yazmin; Iwamoto, Fabio
Abstract: Recurrent glioblastoma has limited therapeutic options. The EF11 trial of TTFs vs. physician's choice chemotherapy showed an objective response rate (ORR) of 14%, but no survival (OS) benefit. CheckMate 143 randomized phase 3, open-label trial of nivolumab vs. bevacizumab failed to show an OS benefit, though nivolumab led to ORR of 7.8% with more durable response than bevacizumab (11.1 vs. 5.3 months). Preclinical studies suggest synergism between TTFs and immunotherapy. TTFs expose calreticulin on cell surfaces, causing HMGB1 and ATP secretion—hallmarks of anticancer immunogenic cell death. Observed trends in a glioma cohort also suggest synergism: 77% of glioma patients treated with TTFs received concurrent temozolomide (16, 31%), nitrosourea (4, 8%), bevacizumab (19, 37%), or immunotherapy (28, 54%). Only 2 (4%) experienced skin toxicity requiring TTFs hold. For TTFs plus immunotherapy vs. chemotherapy, there was a trend toward increased OS (8.3 vs. 6.5 months, p=0.32) and ORR (26% vs. 13%), with significant increase in PFS for glioblastomas (4.6 vs. 3.5 months, p=0.04). ORR was >14% in EF11 or < 5- 10% in meta-analyses of immunotherapy for recurrent glioblastoma. This open-label, phase 2 trial with 2 parallel arms uses a 2-stage Minimax design with stopping rules for futility. We will enroll 30 (15/Arm) to 60 (30/Arm) evaluable subjects. The primary endpoint is ORR by modified RANO. Secondary objectives are OS, PFS, safety, compliance, and biomarker correlations. Adults with glioblastoma at first or second recurrence and no prior CTLA inhibitor or bevacizumab are eligible. All receive TTFs with nivolumab for ≤24 months and ipilimumab for ≤4 doses. Arm A (no prior PD1/PDL1 inhibitor) receive nivolumab only and add ipiliumumab at progression. Arm B (prior PD1/PDL1 inhibitor) receive nivolumab and ipilumimab. Nivolumab is dosed IV q2weeks 240mg as monotherapy and 3mg/kg with ipilumimab IV 1mg/kg q6weeks. TTFs starts by 1 month and worn for ≥75% over ≤24 months.